2011
DOI: 10.1158/0008-5472.can-10-2833
|View full text |Cite
|
Sign up to set email alerts
|

LPS-Induced TLR4 Signaling in Human Colorectal Cancer Cells Increases β1 Integrin-Mediated Cell Adhesion and Liver Metastasis

Abstract: Infectious complications resulting from resection of colorectal cancer (CRC) elevates the risk of cancer recurrence and metastasis, but the reason for this risk relationship is unknown. Defining the mechanisms responsible may offer opportunities to improve outcomes in a majority of patients whose tumors are resected as part of their therapy. The complex formed between Toll receptor TLR4 and myeloid differentiation factor MD2 defines a major cell surface receptor for lipopolysaccharide (LPS), a gram-negative ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
205
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(225 citation statements)
references
References 39 publications
19
205
0
1
Order By: Relevance
“…LPS was shown to increase the invasion of hepatic cancer cells in mice (23) and to potentiate lung metastasis upon intravenous injection of mouse mammary carcinoma cells into animals (24). LPS may contribute to tumor progression by activation of TLR-4 signaling pathway in cancer cells (25) and by the recruitment of inflammatory cells into the tumor microenvironment (26). LPS-induced migration and invasion of inflammatory cells is accompanied by increased production and release of proinflammatory cytokines (27), which display protumorigenic activities (26,28).…”
Section: * This Work Was Supported By the University Medical Center Gmentioning
confidence: 99%
“…LPS was shown to increase the invasion of hepatic cancer cells in mice (23) and to potentiate lung metastasis upon intravenous injection of mouse mammary carcinoma cells into animals (24). LPS may contribute to tumor progression by activation of TLR-4 signaling pathway in cancer cells (25) and by the recruitment of inflammatory cells into the tumor microenvironment (26). LPS-induced migration and invasion of inflammatory cells is accompanied by increased production and release of proinflammatory cytokines (27), which display protumorigenic activities (26,28).…”
Section: * This Work Was Supported By the University Medical Center Gmentioning
confidence: 99%
“…35 Previous study has shown that LPS could increase b1 integrin-mediated cell adhesion and liver metastasis, which was an important marker of EMT. 13 In this study, we treated the colon cancer cells with LPS in vitro to observe the occurrence of EMT, with encouraging results. Stimulation by LPS caused E-cadherin (the epithelial marker) to disappear, Vimentin and Snail (the mesenchymal marker) to increase.…”
Section: Discussionmentioning
confidence: 85%
“…[9][10][11][12] And it could significantly augment the cell adhesion and liver metastasis of human CRC cells. 13,14 Recently, several studies have placed chemokines and their receptors at the center of not only physiological cell migration, but also pathological processes, such as metastasis in cancer. 15 Stromal cell-derived factor 1a (SDF1a)/CXCR4 axis is one of the few chemotactic systems that characterizes one-to-one correspondence reciprocally between the ligand and receptor.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that injection of endotoxin in an experimental model enhanced colon carcinoma cell adhesion in the liver. 51, 52 Importantly, a recent study demonstrated that bowel mobilization already led to bacterial translocation in patients. 40 Furthermore, patients with anastomotic leakage or who encountered bacterial translocation after a colectomy had poor disease-free survival, 41 indicating that bacterial contamination had a negative impact on long-term patient outcome.…”
Section: Discussionmentioning
confidence: 99%